2010
DOI: 10.1021/am100217m
|View full text |Cite
|
Sign up to set email alerts
|

Protecting Polymers in Space with Atomic Layer Deposition Coatings

Abstract: Polymers in space may be subjected to a barrage of incident atoms, photons, and/or ions. Atomic layer deposition (ALD) techniques can produce films that mitigate many of the current challenges for space polymers. We have studied the efficacy of various ALD coatings to protect Kapton polyimide, FEP Teflon, and poly(methyl methacrylate) films from atomic-oxygen and vacuum ultraviolet (VUV) attack. Atomic-oxygen and VUV studies were conducted with the use of a laser-detonation source for hyperthermal O atoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
86
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 26 publications
1
86
0
Order By: Relevance
“…As a consequence, most organic materials onboard spacecrafts and artificial satellites may be rapidly eroded away due to the damage created by those aggressive environmental factors in LEO, especially the AO [5,6]. In LEO, AO may collide with spacecraft surfaces at a high relative velocity of approximately 7-8 km/s, which imparts the equivalent of 4.5-6 eV of translational energy (TE) to AO, thereby causing erosion called AO attack [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, most organic materials onboard spacecrafts and artificial satellites may be rapidly eroded away due to the damage created by those aggressive environmental factors in LEO, especially the AO [5,6]. In LEO, AO may collide with spacecraft surfaces at a high relative velocity of approximately 7-8 km/s, which imparts the equivalent of 4.5-6 eV of translational energy (TE) to AO, thereby causing erosion called AO attack [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Surface bound self-limiting growth with precise thickness control ensures the applicability of ALD in variety of applications [18][19][20][21]. Though the application of ALD in electrochemical storage is overwhelming, but till now the use is mostly limited to the protection layer to enhance the electrochemical performance of the electrode [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…An interesting set of experiments were conducted using Teflon, Kapton, and PMMA in an attempt to imitate and prevent mass loss and erosion due to exposure to the harsh conditions experienced by polymers in low-earth orbit 139 . It was shown that by coating the samples with thin-films of Al 2 O 3 , TiO 2 , or combinations of both that the polymer could be protected from erosion when exposed to atomic oxygen.…”
Section: Coated Synthetic Soft Materialsmentioning
confidence: 99%